Crescimento inicial e consumo hídrico de nim submetido ao estresse salino e biofertilizante bovino - Diniz, Belísia L.M.T.; Cavalcante, Lourival F.; De Mesquita, Francisco O.; De Lima Neto, Antonio J. [UNESP]; Nunes, Járisson C.; Diniz Neto, Manoel A. (Revista Brasileira de Ciencias Agrarias, 2013)
An experiment was carried out during the period of January to July/2010, in municipality of Areia, Paraiba State, Brazil, in order to evaluate effects of the irrigation with saline water, bovine biofertilizer and drainage of the soil on water consumption and growth of neem seedlings. The experimental design was in randomized blocks using factorial 5×2×2, referring to five levels of saline water (0.5; 1.5; 3.0; 4.5; 6.0 dS nr-1) in soil without and with bovine biofertilizer and in pots without and with drainage. In plants the water consumption, growth in height, stem diameter, number of leaves, dry matter of roots, aerial part and total dry mass were evaluated and in soil the electrical conductivity of saturation extract - EC was determined. The bovine biofertilizer, after dilution in non saline water (0.49 dS nr-1) e no chlorinated water in 1:1 ratio was applied once two days before sowing, equivalent to 10% of substrate volume. Irrigation was applied daily with each water type applying volume sufficient to maintain the soil with water content at level of field capacity. From results the increase in salinity of water inhibited the water consumption by plants independently of the soil with or without bovine biofertilizer. The salinity of water in soil with and without bovine biofertilizer also reduced the growth of neem plants but with more pronounced effect in the treatments without application of organic fertilizer to soil in liquid form.
Initial growth and water consumption of neem under salt stress and bovine biofertilizer
Keywords: Indian neem; Organic fertilization; Salinity